PsycEXTRA Dataset 2004
DOI: 10.1037/e463942006-001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Methods for Predicting Performance Impairment Associated With Combat Stress

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, induding the time for reviewing Instructions, searching existing data sources, gathering and maintaining the data needed, and con'leting and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of infomuetion, including suggestions for reducing this burden to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Unlike the other performance measures, Heart Rate variability (HRV) was a significant predictor of False Alarm frequency. This is in contrast to previous findings that Task Engagement predicted False Alarms in vigilance tasks (Matthews et al, 2007). This contrast may be regarded as a form of discriminant validity indicating that the Change Detection task in the present study is not a vigilance task per se.…”
Section: Variable Selection For Regression Analysescontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike the other performance measures, Heart Rate variability (HRV) was a significant predictor of False Alarm frequency. This is in contrast to previous findings that Task Engagement predicted False Alarms in vigilance tasks (Matthews et al, 2007). This contrast may be regarded as a form of discriminant validity indicating that the Change Detection task in the present study is not a vigilance task per se.…”
Section: Variable Selection For Regression Analysescontrasting
confidence: 99%
“…and higher self-report ratings of Task Engagement predicted faster Average response times to correct detections. That Task Engagement was a significant predictor (and not Distress or Worry) suggested that energy, motivation, and alertness impact response times more than components of Distress and Worry, i.e., confidence level and negative affect, or intrusive self-referencing thoughts (Matthews et al, 2007).…”
Section: Variable Selection For Regression Analysesmentioning
confidence: 99%
“…Thus, the effect is directly tied to the mental workload of performing the task, and cannot be attributed to loss of arousal or boredom. Matthews et al (2007; see also Reinerman et al, 2006Reinerman et al, , 2007 conducted two studies that investigated the inter-relationships of TCD, vigilance and subjective measures. The aim was to test whether measurements of TCD might be used to predict subsequent individual differences in vigilance.…”
Section: Cerebral Bloodflow As a Marker For Resourcesmentioning
confidence: 99%
“…However, its neurological bases largely remain to be explored, although, as mentioned, it may plausibly be linked to a dopaminergic reward or approach system. In recent work, we have explored a novel psychophysiological technique for evaluating competence for performing vigilance tasks (Matthews, Warm, & Washburn, 2007;Reinerman et al, 2006). The velocity of bloodflow in the medial cerebral arteries may be measured using transcranial Doppler sonography (TCD: Aaslid, 1986).…”
Section: Cerebral Bloodflow As a Marker For Resourcesmentioning
confidence: 99%
“…Moreover, low affect or motivation is a portent of more significant stress responses, in that it indicates a change in appraisals of stressors. Finally, this predictive power is enhanced when combined with physiological measures (Matthews, Warm, & Washburn, 2007).…”
Section: Tactical Cognitive Readiness Measuresmentioning
confidence: 99%